International Conference on Intelligent Computing and Applications Proceedings of ICICA 2018 - Bhaskar, M. Arun; Dash, Subhransu Sekhar; Das, Swagatam; Panigrahi, Bijaya Ketan (Advances in Intelligent Systems and Computing, 2019)
The book is a collection of best papers presented at the International Conference on Intelligent Computing and Applications (ICICA 2018), held at Velammal Engineering College, Chennai, India on 2-3 February 2018. Presenting original work in the field of computational intelligence and power and computing technology, it focuses on soft computing applications in power systems; power-system modeling and control; FACTS devices - applications in power systems; power-system stability and switchgear and protection; power quality issues and solutions; smart grids; green and renewable energy technologies; optimization techniques in electrical systems; power electronics controllers for power systems; power converters and modeling; high voltage engineering; diagnosis and sensing systems; and robotics.